Implementasi Fungsi Manajemen dalam Meningkatkan Kualitas Keagamaan Perempuan di Majelis Taklim Al-Muhtaram Kajen - Shifa Ismaya; Shilfa Amelia; Shakira Shakira; Chikal Sasmita Sari; Qomariyah Qamariyah (Institut Agama Islam Negeri Kerinci, 2025)
The lack of religious understanding in educating children and maintaining harmony in the family is a crucial issue for women in this modern era. Rapid developments often have a negative impact on spiritual values and family resilience, especially when women, as the main pillars of the household, do not have a strong religious foundation. This phenomenon can be overcome through religious activities, one of which is by attending religious lectures. The purpose of this study is to comprehensively understand the application of management functions in Majelis Taklim at the Al-Muhtaram Kajen Mosque. The subject matter of this study uses management functions (POAC) as the analysis theory. This study uses a qualitative approach. Data collection in this study was carried out using direct observation and interviews with the majelis taklim coordinator. Data analysis was carried out through a process of reduction, presentation, and verification. The results of this study indicate that the implementation of management functions (POAC) in the form of optimal planning, organizing, implementing, and controlling at the Majelis Taklim at the Al-Muhtaram Kajen Mosque can be a means of shaping Muslim women who are resilient, have good character, and are ready to face the challenges of the times.